Sampling Guidelines and Recommendations for Submitting Samples for Diagnosing Laurel Wilt in Avocado Trees (Persea americana L.) - Jonathan Henry Crane; Romina Gazis; Jeff Wasielewski; Daniel Carrillo; Bruce Schaffer; Fredy Ballen; Edward A. Evans (EDIS)
Laurel wilt (LW) is a vascular disease caused by a fungal pathogen transmitted to avocado trees by several ambrosia beetle species and through root grafts among adjacent avocado trees. A critical part of preventing and controlling plant diseases is determining the causal agent so that the appropriate management practices can be implemented to eradicate or contain the outbreak. Proper sampling is a critical step in disease diagnosis and in the determination of the causal agent of disease. This new 3-page publication of the UF/IFAS Horticultural Sciences Department was written by Jonathan Crane, Romina Gazis, Jeff Wasielewski, Daniel Carrillo, Bruce Schaffer, Fredy Ballen, and Edward Evans. https://edis.ifas.ufl.edu/hs1394